Sports in metaphor and metaphor in sports - Dalibor Kesić; Emir Muhić (University of Banja Luka, Faculty of physical education and sport, 2013)
This paper looks at the metaphors and idioms in the English language that have sports as their motivation and attempts to draw certain parallels with their corresponding semantic equivalents in Serbian. To establish the origin of an idiom is not an easy task, it is even more difficult to segregate them in groups relating to the metaphorical motivation. One of the groups that is worth exploring relates to those that seem to be sport generated. They are probably so prevalent among metaphoric constructions on account of their convenience as an interplay between different meanings which at the same is indeed a real play between people. What distinguishes them from other types of expressions is that they include sport terminology while referring to something totally different, sometimes involving ordinary folk, sometimes even state dignitaries. What they all have in common though is the transfer of meaning, from one sematic field into a different arena, this time it being a sport arena. This would imply that phraseology encompasses proverbs, sayings, idiolect and every other form of collocated wording used to denote an object, advice, idea or anything else with a meaning that, to some extent, deviates from the exact meaning of the words used in them. In the methodology chapter, the paper looks at more than 20 different metaphorical sport expressions, while the introduction, results, discussion and conclusion explore the theoretical bases that underpin any twist in meaning once a group of several words are joined together, thereby changing the sum of their individual meanings.